background image

Proof.

We need to prove

h

ν

/∆

i

f

Ob

(

ν

/∆)

g

g

1

ν

f

id

f

Ob

(

ν

/∆)

h

(

ν

/∆)

1

i

g.

Really,

h

ν

/∆

i

f

Ob

(

ν

/∆)

g

ν

f

Ob

(

ν

/∆)

g

g

1

ν

f

id

f

Ob

(

ν

/∆)

h

(

ν

/∆)

1

i

g

f

Ob

(

ν

/∆)

ν

1

g

g

1

ν

f

id

Remark 20.

A way to come to the above formula

x

atoms

∆:

fx

[

ν

]

gx

⇔ ∀

x

atoms

∆:

x

[

g

1

ν

f

]

x

g

1

ν

f

id

.

Hierarchy of singularities

Consider two endo-galufuncoids

µ

and

ν

. Values on Ob

µ

will behave like arguments of functions,

of Ob

ν

like values of functions.

I call SLA

(

Ob

µ

)

singularity level above

Ob

µ

the set of sets of funcoids

ν

f

|

h

µ

i

{

x

}

(or alternatively

of limits xlim

f

|

h

µ

i

{

x

}

) where

f

is a monovalued principal funcoid in

FCD

(

Ob

µ

;

Ob

ν

)

.

[TODO:

Maybe exclude the zero funcoid?]

Consider a galufuncoid

ω

defined by the formulas:

h

ω

i

f

=

ν

f

and

h

ω

1

i

f

=

f

ν

and

f

[

ω

]

g

⇔ ∃

x

Ob

ν

:

g

1

f

id

h

µ

i

{

x

}

FCD

.

We need to prove

h

ω

i

x

ω

g

1

⇔ ∃

x

Ob

ν

:

g

1

(

ν

)

f

id

h

µ

i

{

x

}

and ??

The first is equivalent to

(

ν

)

f

ω

g

1

⇔ ∃

x

Ob

ν

:

g

1

(

ν

)

f

id

h

µ

i

{

x

}

FCD

.

Really,

(

ν

)

f

ω

g

1

⇔ ∃

x

Ob

ν

:

g

1

(

ν

)

f

id

h

µ

i

{

x

}

Lemma 21.

Let

ν

ν

ν

and

ν

1

ν

ν

. If

x

and

y

are ultrafilters, then

x

[

ν

]

y

⇔ h

ν

i

x

=

h

ν

i

y

.

Proof.

[TODO: Prove for the more general case of galufuncoids. It’s problematic.]

x

[

ν

]

y

y

⊑ h

ν

i

x

⇒ h

ν

i

y

⊑ h

ν

ν

i

x

⇒ h

ν

i

y

⊑ h

ν

i

x

. So taking symmetry into account we have

x

[

ν

]

y

⇒ h

ν

i

x

=

h

ν

i

y

.

Let now

h

ν

i

x

=

h

ν

i

y

, Then

y

h

ν

1

ν

i

x

;

y

⊑ h

ν

1

ν

i

x

;

y

⊑ h

ν

i

x

;

y

h

ν

i

x

;

x

[

ν

]

y

.

Theorem 22.

f

[

ν

/

h

µ

i

{

x

}

]

g

ν

f

|

h

µ

i

{

x

}

=

ν

g

|

h

µ

i

{

x

}

for

f , g

SLA

(

Ob

µ

)

.

[TODO:

Generalize it for any

instead of

h

µ

i

{

x

}

?]

Proof.

It’s enough to prove

h

f

i

x

[

ν

]

h

g

i

x

⇔ h

ν

ih

f

i

x

=

h

ν

ih

g

i

x

for every ultrafilter

x

.

h

f

i

x

[

ν

]

h

g

i

x

⇔ h

g

i

x

Ob

µ

h

ν

ih

f

i

x

??

⇒ h

ν

ih

g

i

x

Ob

µ

h

ν

ih

f

i

??

Theorem 23.

SLA

(

Ob

µ

)

is

T

2

-separable.

The reloid

ν

on the set SLA

(

Ob

ν

)

could be defined by one of the two formulas below:

3